Pengaruh Disiplin Kerja Tehadap Kinerja Pegawai Pada Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Sorong - Asmuruf, Evelin Marlin; Suripatty, Roberthair (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
Work discipline is the main motivation that must be possessed by everyone who works or in any organization, whether government or private. And the performance of employees or employees is the main milestone to carry out that discipline, but it is not uncommon for us to find that in the field it is different from the regulations that have been made, this is a problem that must be followed up. Data was collected by questionnaire and interview techniques, In this study, tests have been carried out using methods that strengthen the continuity between work disciplines that affect employee performance. This can be seen from testing using the spss application to test that there is a correlation between work discipline variables and employee performance with a significance value of 0.000 < 0.05. The data obtained is also valid and reliable. The results of the study showed an effect on the data obtained.